1994
DOI: 10.1021/bi00185a003
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Aminoacylated RNAs as Efficient Substrates for Elongation Factor Tu

Abstract: We demonstrate here, using RNA variants derived from tRNAAsp, that the minimalist aminoacylated structure able to interact efficiently with elongation factor Tu comprises a 10 base-pair helix linked to the 3'-terminal NCCA sequence. Shorter structures can interact with the elongation factor, but with significantly decreased affinity. Conserved features in the aminoacyl acceptor branch of tRNAs, such as base pair G53-C61 and the T-loop architecture, could be replaced respectively by the inverted base pair C53-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…reducing translation accuracy) consequently leading to temperature sensitivity. Previous studies have indicated, however, that in vitro tRNAs lacking ψ55 are used in translational elongation with an efficiency indistinguishable from wild-type tRNAs (Nazarenko et al, 1994 ;Rudinger et al, 1994). Measurements of translational accuracy using β-galactosidase thermal lability did not show any indication of misreading occurring in a truB mutant (data not shown), although subtle changes would not be detected with this assay.…”
Section: Discussionmentioning
confidence: 66%
“…reducing translation accuracy) consequently leading to temperature sensitivity. Previous studies have indicated, however, that in vitro tRNAs lacking ψ55 are used in translational elongation with an efficiency indistinguishable from wild-type tRNAs (Nazarenko et al, 1994 ;Rudinger et al, 1994). Measurements of translational accuracy using β-galactosidase thermal lability did not show any indication of misreading occurring in a truB mutant (data not shown), although subtle changes would not be detected with this assay.…”
Section: Discussionmentioning
confidence: 66%
“…Similar stemloops and primary structure are not found in the 5'UTRs of, for example, poliovirus and FMDV. The idea of binding of eIF-2 binding to these sequences in the EMC S'UTR does not conflict with results on minimal requirements of tRNAAsP-binding by EF-Tu [29] and the structural similarities between eIF-2y and EF-Tu [30]. The binding site for EF-Tu in tRNA also resides in the 3' terminal part of the molecule [29].…”
Section: Basepairing Around Aucymentioning
confidence: 89%
“…The possible importance of tRNA conformation at the end of the acceptor stem and near the junction of the acceptor stem-T⌿C stem extended helix for binding to the EF can be understood from the crystal structure of the T. thermophilus EF-Tu ⅐ GDPNP ⅐ aminoacyl-tRNA ternary complex (44,45) and previous work on the region of the tRNA involved in binding to EF-Tu and eEF1 (27,28,51). With the exception of the 3Ј-terminal A and the aminoacyl-ester group, in the crystal structure, EF-Tu makes no base-specific contacts with the tRNA.…”
Section: Discussionmentioning
confidence: 99%